ANALISIS EFISIENSI BIAYA DAN KEUNTUNGAN USAHA SUSU KAMBING PERANAKAN ETAWA DI KECAMATAN KALIGESING KABUPATEN PURWOREJO (STUDI KASUS 4 PERUSAHAAN DI KECAMATAN KALIGESING) - Wihandoyo, Dika; Wakhidati, Yusmi Nur; Subagyo, Yusuf (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. This study aims to calculate revenue, total costs, profits and efficiency analysis seen from the R/C Ratio of the Etawa crossbreed goat milk business on a small scale and large scale business in Kaligesing sub-district, and to see whether there is an effect of the relationship between efficiency analysis and large scale business. small business scale by using the Independent Sample t test. Materials and methods. The sampling method of respondents used a purposive sampling method (deliberately), namely the area that has a commercial Etawa crossbreed goat milk business. Collecting data using the Survey Method, namely conducting interviews with the help of questionnaires and direct field observations. Results. The results of the previous survey found that there were dairy companies, namely Cipta Mandir, Wiranto Farm, Kaisa Farm and Goat-Milk. The results of the research on the acceptance of the 2 business scales on average, namely the small business scale of IDR 63,525,000 / period and the large business scale of IDR 193,950,000 / period. The total cost on a small scale business is IDR 47,335,000 / period and a large business scale of IDR 140,260,000 / period. The profit on a small scale business is IDR 16,190,000 / period and a large business scale of IDR 53,690,000 / period. The results of the analysis of the R/C ratio of the Etawa crossbreed goat milk business on a small and large scale on average are 1.34 and 1.38. The results of the t-test or difference analysis show that there is no difference in profits and R/C ratio between small and large scale businesses.